How to cheat in Photoshop Elements 11 release your imagination - Asch, David (Focal Press, 2013)
"Have you ever wanted to summon magical powers? Create a stained glass style masterpiece? Or turn Summer into Fall? There's a whole world of opportunity out there for creating fun photomontages, powerful panoramas, and dynamic distortions. Redesigned and completely rewritten for Elements 11, this book starts you at the basics of photomontage with selection techniques, layers and transformations; leading up to full-length projects for creating magazine covers, fantasy scenes, poster artwork and much, much more. This book also features: - A dedicated website where you can download images and tutorial videos that show you how to expand, develop, and master top techniques. - Full color images, a glossary of terms, useful keyboard shortcuts, and a detailed index that will help you locate that fantastic technique in a flash. David Asch is an author and freelance journalist specializing in Photoshop and Photoshop Elements image editing and manipulation"--Provided by publisher.